THE IMPORTANCE OF SFAS NO. 1 APPLICATION AND ITS EFFECT TOWARD LIABILITIES OF FINANCIAL STATEMENT PREPARATION: (Case Study On UD . Victory Motor In Surabaya) - Neno Aga Dirhayu; Diana Zuhroh (Fakultas Ekonomi Universitas 45 Surabaya, 2013)
The financial statements will be considered reasonable if its presentation had been in accordance with Financial Accounting Standards which is generally accepted or commonly referred as SFAS compiled by IAI and the characteristics of those financial statements should be understandable, relevant, reliable, and comparable. In preparing the financial statements there are rules for recording transactions, which are the pairs bookkeeping system (double entry), this recording system is a common and commonly used in the preparation of the financial statements. The preparation of financial statements that was often still used is the single bookkeeping system (single entry), when the records did not show a complete overview of the transaction, then in order to preparing the financial statements that would be considered be reasonable will meet the difficulties, other than there is no direct way to know whether the balances was right, so the company is faced the danger of deviation, inaccurate, which those financial statements are not in accordance with accounting standards. In achieving the purposes of this study, then financial statements that has been adapted to the provisions of SFAS No. 1 will be restated based on the data that obtained from the company by using the pairs bookkeeping system (double entry), and secondly to determine the effect that raised when the financial statements are in accordance with provisions of SFAS No. 1. For this discussion, the researcher was restated the financial statements of the company in 2012. From the results of those financial statements presentation it will seem easier to be read by the parties who need financial statements to make economic decision-making in the present and in the future. Researcher has suggested that the company's financial statements presentation was able to present in accordance with SFAS No. 1 by using the pairs bookkeeping system (double entry).